The Relationship Of Explosive Leg Muscle Power And Leg Length With Long Jump Results In Students Private Class Viii1 SMP Negeri 6 Siak Hulu - Ardison, Ardison; Ahmad Rahmadani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The aim of this research is to determine the relationship between leg muscle explosive power and leg length with long jump results in students son of class VIII1 of SMP Negeri 6 Siak Hulu. This type of research is multiple correlation. The population and sample in this study were 17 male students in class VIII1 of SMP Negeri 6 Siak Hulu. The research instruments used were the standing broadjump test, leg length test and long jump test. The data analysis technique used is the multiple correlation value test. Based on the results of the research that has been carried out, it can be concluded that; 1) There is a relationship between explosive power of leg muscles and long jump results in students son of class VIII1 of SMP Negeri 6 Siak Hulu with a calculated r greater than r table ( 0.571 > 0.482), 2) There is a relationship leg length with long jump results in students son of class VIII1 of SMP Negeri 6 Siak Hulu with a calculated r greater than r table (0.648 > 0.482), 3) There is a relationship between explosive power of leg muscles and leg length with long jump results in students son of class VIII1 of SMP Negeri 6 Siak Hulu with a calculated r greater than r table ( 0.755 > 0.482).